Rancang bangun model rantai pasok halal Ayam Joper: Integrasi HAS 23000, SNI 99002:2016, dan Model SCOR - Muhammad Fitri Budi Utomo; Siti Dinar Rezki Ramadhani (Nur Science Institute, 2025)
This study aims to design a halal supply chain model for Joper chicken by integrating the Halal Assurance System (HAS 23000), the Indonesian National Standard for halal poultry slaughtering (SNI 99002:2016), and the Supply Chain Operations Reference (SCOR) model. The research identifies ten Halal Critical Points (HCPs) along the supply chain from upstream to downstream. Through direct observation, interviews with stakeholders (farmers, brokers, poultry slaughterhouse operators, and restaurant owners), and literature review, this study identifies potential risks that could threaten halal status. A total of 31 risk events were mapped using the guidelines from SNI 99002:2016. The SCOR model was then applied to systematically structure the halal supply chain framework based on five pillars: Plan, Source, Make, Deliver, and Return. The result is a comprehensive and integrated halal supply chain model that enhances traceability, control, and assurance of halal integrity in the Joper chicken business processes. The proposed halal supply chain model enhances traceability, halal quality control, and risk management across all stages. This model serves as a valuable reference for industry practitioners and policymakers to strengthen halal assurance systems in Indonesia's poultry sector.